Clinical profile of heart failure in Beta-Thalassaemia Major (ß-TM): Case studies with current consideration and future perspectives - Sanzgiri, Prakash; Agarwal, Mohan; Reddy, Charan; Potdar, Priytanka (SA Heart Journal, 2022)
Background: Cardiac involvement is a major cause of mortality in Beta-Thalassaemia Major (ß-TM) patients. Despite many advances in therapeutic management of ß-TM, cardiac involvement remains the primary cause of mortality in ~70% of the cases. Chronic iron overloading results in thalassaemic cardiomyopathy, leading to diastolic dysfunction and overt heart failure (HF). Serial electrocardiography (ECG), 2D-echocardiography (2DECHO) and cardiovascular magnetic resonance (CMR) help in early detection and risk stratification of ß-TM patients, to prevent complications, such as arrhythmias and sudden cardiac death. An established network of care between thalassaemia centres and local health providers is essential for optimal management. Case presentation: We report 2 cases of HF in ß-TM of varied etiology, and different approaches undertaken for its early diagnosis and treatment. Conclusion: It is important to differentiate various phenotypes of cardiomyopathy in ß-TM. Since, the management of each varies accordingly. ß-TM patients require a multi-disciplinary approach that includes HF specialists, haematologist, hepatologist, endocrinologist, psychologist, transfusion experts and nursing personnel to maximise benefits from the application of the modern HF therapeutic strategies in evaluation, monitoring and treatment. SAHeart 2022;19:14-18